Optical property modification of ruby and sapphire by N-ion implantation - Chaiwong C. (2014)
Effects of N-ion implantation on surface modification of synthetic single crystalline ruby (Cr-doped Al2O3) and sapphire (α-Al2O3) were studied. N ions at energy 120 keV were implanted to samples with doses ranging from 1×1016 to 1×1018 ions/cm2. Temperature studies ruled out the effect of ion-beam heating and, therefore, the gemological modification was the direct result of the implanted ions and radiation damage. Optical measurements showed that the optical absorption of the ion-implanted ruby uniformly increased without observable characteristic changes in any wavelength bands, whereas for the high-dose ion-implanted sapphire, optical absorption in the short wavelength region became stronger. The refractive indices however showed the same decreasing trend in the higher dose ion-implanted samples for both types of crystals. N-ion implantation also caused blistering of the surface, as studied by scanning electron microscopy (SEM). The medium-dose (5×1017 ions/cm2) ion-implanted surfaces started to show drastic blistering, and the high-dose (1×1018 ions/cm2) ion implantation further resulted in amorphization of the ruby and sapphire surfaces. According to these data, the optical property changes are then attributed to the gem-material surface modification. © 2004 Elsevier B.V. All rights reserved.